TENDENCIES OF DEVELOPMENT OF FOREIGN INVESTMENT IN THE WORLD MARKET OF SERVICES OF THE INDUSTRIAL CONSTRUCTION - I. Kovalev (Вестник университета, 2016)
In the modern structure of the world market of construction services the increasing role is played by services of an industrial construction. Complication of relations between customers and contractors in this market is observed. In this article the main tendencies of attraction of foreign investments in the international market of services of an industrial construction are analysed.